The data acquisition system of the Latin American Giant Observatory (LAGO) - Sofo Haro, Miguel Francisco; Arnaldi, Luis Horacio; Alvarez, W.; Alvarez, C.; Araujo, C.; Areso, Omar Antonio; Asorey, Hernán Gonzalo; Audelo, M.; Barros, H.; Bertou, Xavier Pierre Louis; Bonnett, M.; Calderon, R.; et al. (Elsevier Science, 2016)
Fil: Sofo Haro, Miguel Francisco. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina